LCMS dataset on compounds in syzygium polyanthum (wight) walp. leaves variant from the East coast of Peninsular Malaysia - T. Anuar, T.A. Faiz; Ismail, Azlini; Mohamed Suffian, Izzat Fahimuddin; Abdul Hamid, Azzmer Azzar; Arzmi, Mohd Hafiz; Omar, Muhammad Nor (2021)
The data presented here is the liquid chromatography and mass spectrometry (LC-MS) profile of phytochemical com- pounds in the aqueous extract of Syzygium polyanthum (Wight) Walp. leaves. This plant is consumed raw and some- times added to local dishes of people in Southeast Asia coun- tries. Most importantly, it has ethnomedicinal values mainly in treating diabetes and hypertension, and at the same time, this plant has anti-microbial, anti-oxidant, anti-cancer, and anti-tumor properties [1] . There are chemical composition variations reported between the same species of different ge- ographical locations, which eventually affect the plant’s ther- apeutic potential [2,3] . This dataset represents the identified compounds for S. polyanthum (Wight) Walp. leaves, a variant collected from Kuantan, a city located in the Pahang state on the East Coast of Peninsular Malaysia. The leaves were then dried in an open-air at room temperature for three weeks, ground, and then macerated in water inside a bath-sonicator, freeze-dried, and then run using LCMS. The LCMS was run using the ultra-performance liquid chromatography equipped with an electrospray time-of-flight mass spectrometer detec- tor, operated in a negative-ion mode. The mass spectral fea- tures from samples raw data were matched with Traditional Medicine (en) and Waters Screening libraries in the Waters UNIFI TM Scientific Information System software version 1.7 (Waters, USA) for compounds identification.